2020
DOI: 10.1017/s1744133120000225
|View full text |Cite
|
Sign up to set email alerts
|

Learning from health system reform trajectories in seven Canadian provinces

Abstract: In publicly funded health systems, reform efforts have proliferated to adapt to increasingly complex demands. In Canada, prior research (Lazar et al., 2013, Paradigm Freeze: Why is it so Hard to Reform Health Care in Canada?, McGill-Queen's Press) found that reforms at the end of the 20th century failed to change the fundamentals of the Canadian system based on physician independence and assured universal coverage only for medical and hospital services. This paper focuses on reforms since the turn of the mille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Despite Quebec's attempts over time to re‐balance the distribution of resources across sectors of care, 3 the first wave of the pandemic revealed persistent difficulties in responding to needs in LTC settings, home care and in deprived areas. A recent report by the Protecteur du citoyen 33 concluded that the government invested efforts in preparing hospitals for the pandemic, but paid little policy attention initially to other sectors of care.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite Quebec's attempts over time to re‐balance the distribution of resources across sectors of care, 3 the first wave of the pandemic revealed persistent difficulties in responding to needs in LTC settings, home care and in deprived areas. A recent report by the Protecteur du citoyen 33 concluded that the government invested efforts in preparing hospitals for the pandemic, but paid little policy attention initially to other sectors of care.…”
Section: Resultsmentioning
confidence: 99%
“…Shortages in various occupational categories are a long-standing issue in Quebec's health system. [34][35][36] As in other Canadian provinces, the system developed historically around two main centres of gravity-medical and hospital care-guaranteed under the Canada Health Act, 3 which has had the effect of limiting the attention paid to emerging health priorities such as care for a growing vulnerable elderly population.…”
Section: System Integrationmentioning
confidence: 99%
See 2 more Smart Citations
“…While emergencies have increased in frequency, they may still be rare in certain regions of Canada which leads to variability in the commitment of leadership to invest in preparedness [ 10 ]. Another element of variation stems from the nature of health systems in each region of Canada [ 51 ]. Alberta has a long history of responding to natural disasters including fires and floods which has seen the development of a robust emergency planning and co-ordination capability [ 52 ].…”
Section: Discussionmentioning
confidence: 99%